The prevalence and clinical associations of HTLV‐1 infection in a remote Indigenous community. Issue 7 (3rd October 2016) - Einsiedel, Lloyd J; Pham, Hai; Woodman, Richard J; Pepperill, Clinton; Taylor, Kerry A
Abstract: Objective: Hospital and laboratory data indicate that human T‐lymphotropic virus type 1 (HTLV‐1) is endemic to central Australia, but no community‐based studies of its prevalence or disease burden have been reported. We determined the prevalence rates of HTLV‐1 infection and of HTLV‐1‐associated diseases in a remote Indigenous community. Setting: A remote Northern Territory community. Design: All residents were asked to complete a health survey and offered a limited clinical examination, together with serological tests for HTLV‐1 and Strongyloides, and HTLV‐1 proviral load (PVL) assessment. Main outcome measures: HTLV‐1 seropositivity rates; HTLV‐1 PVL (copies/105 peripheral blood leucocytes [PBL]); presentation with HTLV‐1‐related clinical disease. Results: HTLV‐1 serostatus was determined for 97 of 138 residents (70%). The prevalence of HTLV‐1 infection was significantly higher among adults (30 of 74 people tested) than children (1 of 23; P = 0.001). Nine of 30 HTLV‐1‐positive adults had a clinical syndrome that was potentially attributable to HTLV‐1 infection (chronic lung disease, seven; symptomatic strongyloidiasis, two). The median HTLV‐1 PVL was significantly higher for adults with chronic lung disease than for those who were asymptomatic (chronic lung disease, 649 copies/105 PBL [IQR, 162–2220]; asymptomatic adults, 40 copies/105 PBL [IQR, 0.9–229]; P = 0.017). Ten of 72 adults tested were seropositive for Strongyloides (six of 28 HTLV‐1‐positive participants and four of 44 HTLV‐1‐negative participants; P = 0.17), as were three of 15 children tested; the three children were HTLV‐1‐negative. Conclusion: The prevalence of HTLV‐1 infection and the rate of disease potentially attributable to HTLV‐1 were high among adults in this remote community.